(untitled) (Bangladesh Journal of Agricultural Research, 2013)
A field experiment on intercropping of okra and leafy vegetables was conducted at Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur and Agricultural Research Station, Burirhat, Rangpur during Kharif-I season of 2010 and 2011 to find out suitable crop combination for higher productivity and economic return. Seven treatments viz., sole okra (50 cm × 40cm), okra 100% (in row) + red-amaranth 100% (broadcast), okra 100% (in row) + red-amaranth 75% (broadcast), okra 100% (in row) + leaf amaranth 100% (broadcast), okra 100% (in row) + leaf amaranth 75% (broadcast), okra 100% (in row) + jute as patshak 100% (broadcast), okra 100% (in row) + jute as patshak 75% (broadcast) were used. Intercropping reduced okra yield but total productivity increased due to additional yield of vegetables. In both the locations, sole okra produced the highest yields (15.82 t/ha at Joydebpur and 13.79 t/ha at Burirhat). Among the intercropping treatments, the highest okra yields (15.42 t/ha at Joydebpur and 12.64 t/ha at Burirhat) were obtained from okra 100%+ red amaranth 75% combination. The lowest okra yield (13.16 t/ha at Joydebpur and 11.75 t/ha at Burirhat) was recorded in okra 100% + jute as patshak 100% combination. The highest okra equivalent yield (23.00 t/ha) was recorded in okra 100% + red amaranth 100% at Joydebpur and in okra 100% + leaf amaranth 100% (21.79 t/ha) at Burirhat. These treatment combinations also gave the highest gross margin (Tk. 227180/ha at Joydebpur and Tk. 214600/ha at Burirhat) and benefit cost ratio (5.66 at Joydebpur and 5.58 at Burirhat). The results revealed that cent percent red amaranth (broadcast) or leaf amaranth intercropped with cent percent okra might be suitable combination for higher productivity and economic return at Joydebpur and Burirhat, respectively. Bangladesh J. Agril. Res. 38(1): 137-143, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15199